Inert liquid exfoliation and Langmuir-type thin film deposition of semimetallic metal diborides - Synnatschke, Kevin; Müller, Alina; Gabbett, Cian; Mohn, Michael Johannes; Kelly, Adam G.; Mosina, Kseniia; Wu, Bing; Caffrey, Eoin; Cassidy, Oran; Backes, Claudia; Sofer, Zdenek; Kaiser, Ute; et al. (ACS nano, 2024)
Graphite is one of only a few layered materials that can be exfoliated into nanosheets with semimetallic properties, which limits the applications of nanosheet-based electrodes to material combinations compatible with the work function of graphene. It is therefore important to identify additional metallic or semimetallic two-dimensional (2D) nanomaterials that can be processed in solution for scalable fabrication of printed electronic devices. Metal diborides represent a family of layered non-van der Waals crystals with semimetallic properties for all nanosheet thicknesses. While previous reports show that the exfoliated nanomaterial is prone to oxidation, we demonstrate a readily accessible inert exfoliation process to produce quasi-2D nanoplatelets with intrinsic material properties. For this purpose, we demonstrate the exfoliation of three representative metal diborides (MgB2, CrB2, and ZrB2) under inert conditions. Nanomaterial is characterized using a combination of transmission electron microscopy, scanning electron microscopy, atomic force microscopy, IR, and UV-vis measurements, with only minimal oxidation indicated postprocessing. By depositing the pristine metal diboride nanoplatelets as thin films using a Langmuir-type deposition technique, the ohmic behavior of the networks is validated. Furthermore, the material decomposition is studied by using a combination of electrical and optical measurements after controlled exposure to ambient conditions. Finally, we report an efficient, low-cost approach for sample encapsulation to protect the nanomaterials from oxidation. This is used to demonstrate low-gauge factor strain sensors, confirming metal diboride nanosheets as a suitable alternative to graphene for electrode materials in printed electronics.
Gesehen am 05.05.2025